Judo Kumi-te pattern and technique effectiveness shifts after the 2013 International Judo Federation rule revision - Ito, K.; Hirose, N.; Nakamura, M.; Maekawa, N.; Tamura, M. (Archives of Budo, 2014)
Background & Study Aim: Breaking the opponent`s grasp using both hands, failure to engage the opponent promptly at the outset of the match, and delaying the progression of the competition through evading the opponent`s attempts at kumi-te all became prohibited under a 2013 rule revision. Violations of these rules result in a shido penalty. This rule revision will affect both the application frequency of kumi-te and competitors` technique selection and attack patterns. Previous studies have not explored the relationship between kumi-te and the effectiveness of throwing techniques in full. This study aim is a knowledge about the effects of kumi-te, with an emphasis on application frequency, on scored techniques through a comparative analysis of matches before and after the 2013 rule revision. Material & Methods: Three hundred eighty six men`s contests from the 2012 Grand Slam Tokyo and 2013 Grand Slam Paris were examined using All Japan Judo Federation DVDs. Data used in the analysis was taken only from techniques that were scored. The attack efficiency index formula introduced by Adam and a t-test were used in combination to conduct a comparative analysis of the contests. Results: Techniques performed after three applications of kumi-te resulted in significantly higher attack efficiency indexes for 2013 competitions compared to those in 2012 (P<0.01). Specifically, the attack efficiency index results were significantly higher in regards to combination, counter, and yoko-sutemi-waza tactics (P<0.05, P<0.05, P<0.01, respectively). Conclusions: Based on the results of this study, it is recommended that judo practitioners and their trainers develop new strategies that incorporate three applications of kumi-te. Furthermore, technique selection and tactical planning to counter anticipated changes in opponent`s techniques after rule revisions are crucial to scoring in and winning contests.